EPIDEMIOLOGICAL ANALYSIS OF DENGUE CASES IN THE CITY OF SÃO MATEUS - ESPÍRITO SANTO - Peruch, Paula Carolina; de Oliveira Souza, Nayana; Guimarães, Djane Lobo; Cortelette, Natália Alves; de Freitas, Rodrigo Randow; Trés Pancoto, João Alexandre (Brazilian Journal of Production Engineering, 2019)
Dengue is an infectious disease transmitted by the mosquito bite of the genus Aedes. The disease can be caused by any of the serotypes, which can be asymptomatic to a clinical picture ranging from simple fever to classic dengue fever (FD) to severe hemorrhagic fever. It is currently a major public health problem worldwide. The municipality of São Mateus is one of the Brazilian cities, which are located in regions of intense vector proliferation. Our study performed an epidemiological analysis of cases of dengue in São Mateus, using methodology of Geographic Information System (GIS) in the period 2008-2014. Dengue prevails in areas of greater population density, inhabited by people of low income, where sanitation infrastructure is precarious. Contrary to this situation, the areas with higher income and recent occupation, with low densification index, presented less recorded cases of dengue.: The research, therefore, was able to specifically delineate the region’s most affected by the dengue virus. It is possible to understand the real situation of the dengue virus in the municipality, and to facilitate the decision-making of the managers to raise effective strategies that reflect the reduction of rates of disease.